Clinical Presentations of Chagas Cardiomyopathy. (4th November 2020) - Shehadeh, Malik; Barac, Ana; Marcus, Rachel
Abstract : Chronic Chagas cardiomyopathy (CCC) is the most common cause of nonischemic cardiomyopathy in endemic Latin American countries. Immigrants to the United States suffer from this disease, but it is underrecognized. We describe the three hallmark clinical presentations: stroke, ventricular arrhythmias, and heart failure, which should prompt suspicion for CCC.